Development of thermotolerant strain of S. cerevisiae for the sacrification and simultaneous fermentation of lignocellulosic biomass : Desenvolvimento de linhagens termotolerantes de S. cerevisiae visando a sacarificação e fermentação simultânea da biomassa lignocelulósica - Mélo, Allan Henrique Félix de, 1993- (2019)
Orientador: Rosana Goldbeck